From ideas to action governance paths to net zero - Sarra, Janis Pearl 1954- (Oxford University Press, 2020)
This book offers a guide, for companies, pension funds, asset managers, and other institutional investors, on how to commence the legal, governance, and financial strategies needed for effective climate mitigation and adaptation, and to help distribute the economic benefits of these actions to their stakeholders. It takes the reader from ideas to action, from first steps to a more meaningful contribution to the move towards a net zero carbon world. It can serve as a helpful guide to everyone implicated in a corporation's activities - employees, pensioners, consumers, banks and other lenders, policymakers, and community members. It offers insights into what we should be expecting, and asking, of these fiduciaries who have taken responsibility for effectively managing our savings, our retirement funds, our investments, and our tax dollars.